Examining Ethical Conduct Among Employees and Governance Standards in Suryabinayak Municipality, Bhaktapur, Nepal: A Case Analysis - Bhandari, Rita (Journal of Kathmandu BernHardt College, 2023)
This study investigates the crucial role of ethical conduct among public sector employees in Suryabinayak Municipality, Bhaktapur, Nepal, aiming to improve local government service delivery. Findings indicate satisfactory levels of ethical behavior, awareness of good governance principles, and transparency. However, challenges such as corruption, political interference, and bureaucratic obstacles persist, hindering effective governance. Recommendations emphasize the importance of ethical behavior to ensure equity, transparency, and quality in local government services. The study adopts a mixed-method approach, combining quantitative analysis with qualitative insights gathered through questionnaires and interviews.